2015
DOI: 10.5433/1679-0359.2015v36n1p431
|View full text |Cite
|
Sign up to set email alerts
|

Glicerina bruta na dieta de ovinos confinados: Composição centesimal e perfil de ácidos graxos do longissimus dorsi

Abstract: ResumoObjetivou-se avaliar a composição centesimal e o perfil de ácidos graxos do longissimus dorsi de ovinos alimentados com dietas contendo níveis crescentes (0; 2,65; 5,33 e 8,06% da matéria seca) de glicerina bruta (GB). Foram utilizados 20 cordeiros mestiços Santa Inês x Dorper, machos castrados, com 24 ± 2,0 kg e alojados em baias individuais. O delineamento utilizado foi inteiramente casualizado, com quatro tratamentos e cinco repetições. Amostras das dietas ofertadas foram coletadas para avaliar a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
1
1
1
Order By: Relevance
“…According to Leão et al (2011), the most abundant saturated acids in lamb are myristic (C14:0), palmitic (C16:0) and stearic acids (C18:0); besides the monounsaturated palmitoleic (C16:1n7) and oleic acids (C18:1n9), and polyunsaturated linoleic (C18:2n6), linolenic (C18:3n3) and arachidonic acids (C20:4n6). Barros et al (2015) studied the addition of crude glycerin in lambs' diet and found 27 fatty acids in meat composition, with greater representation also for oleic acid (18:1n9), stearic acid (18:0), and palmitic acid (16:0), confirming the results of this study. Regarding the monounsaturated fatty acids identified in the meat fat, oleic acid was considered as the monounsaturated fatty acid with higher expression levels in ruminants.…”
Section: Parameterssupporting
confidence: 78%
See 2 more Smart Citations
“…According to Leão et al (2011), the most abundant saturated acids in lamb are myristic (C14:0), palmitic (C16:0) and stearic acids (C18:0); besides the monounsaturated palmitoleic (C16:1n7) and oleic acids (C18:1n9), and polyunsaturated linoleic (C18:2n6), linolenic (C18:3n3) and arachidonic acids (C20:4n6). Barros et al (2015) studied the addition of crude glycerin in lambs' diet and found 27 fatty acids in meat composition, with greater representation also for oleic acid (18:1n9), stearic acid (18:0), and palmitic acid (16:0), confirming the results of this study. Regarding the monounsaturated fatty acids identified in the meat fat, oleic acid was considered as the monounsaturated fatty acid with higher expression levels in ruminants.…”
Section: Parameterssupporting
confidence: 78%
“…Moisture content was 69.9 g 100 g -1 which is below the findings of Zeola et al (2004), who found 75.6 g 100 g -1 , but close to the findings of Barros et al (2015), who also evaluated increasing levels of crude glycerin on diet and found values ranging from 67.7 to 72.2 g 100 g -1 . The total lipids and crude protein levels averaged 3.47 and 20.05 g kg -1 , respectively (Table 3) and are close to the values obtained by Ortiz et al (2005), being consistent with good quality meat, and considered acceptable in the literature.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…Os principais ácidos graxos encontrados na carne de ovinos são o C16:0 (20,11% -24,80%), C18:0 (16,98% -31,05%) e C18:1 (32,61% -46,40%) (46)(47)(48). Os AGS dessa espécie variam entre 40-49% do total de AG.…”
Section: áCidos Graxos Da Carne De Ruminantesunclassified